Preferential Feline Immunodeficiency Virus (FIV) Infection of CD4(+) CD25(+) T-Regulatory Cells Correlates both with Surface Expression of CXCR4 and Activation of FIV Long Terminal Repeat Binding Cellular Transcriptional Factors - Joshi, Anjali (American Society for Microbiology, 2005)
Previously, we have characterized feline CD4(+) CD25(+) T-regulatory (Treg) cells with regard to their immune regulatory properties and ability to support feline immunodeficiency virus (FIV) replication in vitro and in vivo. Our studies showed that while CD4(+) CD25(+) cells were capable of replicating FIV in the presence of interleukin-2 (IL-2) alone, CD4(+) CD25(−) cells harbored a latent infection that required a strong mitogenic stimulus to activate virus replication. In the present study, we investigated the mechanisms governing the preferential replication of FIV in highly purified CD4(+) CD25(+) Treg cells compared to their CD4(+) CD25(−) counterparts. Studies aimed at elucidating mechanisms regulating infection of these cells revealed that CD4(+) CD25(−) cells were less susceptible to FIV binding and entry than CD4(+) CD25(+) cells, which correlated with increased surface expression of FIV coreceptor CXCR4. In addition, the number of CD4(+) CD25(+) cells that expressed the primary receptor CD134 was greater than for CD4(+) CD25(−) cells. Although increased permissiveness to FIV infection of CD4(+) CD25(−) cells following mitogenic stimulation correlated strongly with upregulation of surface CXCR4, it did not correlate with CD134 expression. Further, study of intracellular factors regulating FIV replication revealed that CD4(+) CD25(+) but not CD4(+) CD25(−) T cells showed constitutive and IL-2-responsive transactivation of activating transcription factor, CAAT enhancer binding protein, and activating protein 1 transcription factors that are important for FIV replication. These factors were upregulated in CD4(+) CD25(−) T cells following ConA stimulation, which correlated with FIV replication. This is the first report elucidating the mechanisms that allow for productive lentiviral infection of CD4(+) CD25(+) Treg cells.